Estudo qualitativo e iconográfico de calçados femininos sobre ocasião de uso e profissões - Barbone, Denise de Barros Camargo (2017)
This research aimed to understand the use of women's shoes, especially at work and in leisure situations, and relate them to the professions of their consumers. For this, a qualitative study was carried out with 30 middle- and upper-class women working in five professional areas, with the aid of an electronic journal. The central premise of this study is a possible association between the areas of professional activity of these women with the style of shoes used on different occasions. Thus, there should be a predisposition for women to adapt footwear styles and heel sizes (modern, classic, fashion, high, and low) to the type of job performed. The results indicated that even professionals in the same area, such as education professionals, adopt different styles of footwear, expressing the individuality of each consumer. In professions, whose work place requires specific dress codes and greater practicality when walking, such as for lawyers, classic shoes prevailed? Freelance professionals such as stylists and designers, considered their individual styles as a major factor in their choices, with a more fashionate style for an English teacher or modern for a designer professional, and the heels were either very high or no present at all. The results show that there is no apparent correlation between profession and the style of footwear used. However, the use of high heels was decisive at work place in all professions . An in-depth study should be conducted in order to test how the propositions raised by this survey could allow the results to be applied by women's shoes manufacturers and retailers.